2019
DOI: 10.3390/jcm8060826
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Genomic Medicine in the Therapeutic Management of Rheumatoid Arthritis

Abstract: During the last decade, important advances have occurred regarding understanding of the pathogenesis and treatment of rheumatoid arthritis (RA). Nevertheless, response to treatment is not universal, and choosing among different therapies is currently based on a trial and error approach. The specific patient’s genetic background influences the response to therapy for many drugs: In this sense, genomic studies on RA have produced promising insights that could help us find an effective therapy for each patient. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…97,98 Although the causal connection between the genetic variant and aberrant cytokine production was not explored mechanistically in this patient, nor was the distribution among the different cell types characterized, the demonstration of the abnormal cytokine secretion was necessary to guide the treatment to the appropriate biologic, as the identification of a genetic variant alone was insufficient to guide the treatment, making complementary strategies necessary. 99 This case report suggests that PBMCs cytokine secretome may be useful to personalize the appropriate biologic treatment. It also shows the importance of diagnosis of the autoinflammatory part of an autoimmune disease, even though it is not necessarily representative of the inflammatory tissues, nor does it provide mechanistic insight into the disease.…”
Section: Why When and How To Evaluate Cytokines?mentioning
confidence: 88%
See 1 more Smart Citation
“…97,98 Although the causal connection between the genetic variant and aberrant cytokine production was not explored mechanistically in this patient, nor was the distribution among the different cell types characterized, the demonstration of the abnormal cytokine secretion was necessary to guide the treatment to the appropriate biologic, as the identification of a genetic variant alone was insufficient to guide the treatment, making complementary strategies necessary. 99 This case report suggests that PBMCs cytokine secretome may be useful to personalize the appropriate biologic treatment. It also shows the importance of diagnosis of the autoinflammatory part of an autoimmune disease, even though it is not necessarily representative of the inflammatory tissues, nor does it provide mechanistic insight into the disease.…”
Section: Why When and How To Evaluate Cytokines?mentioning
confidence: 88%
“…The TRAF6‐independent overproduction of IL‐6 could be attributed to TRAF2 and TRAF5, as it was shown that both factors could transduce the IL‐17 signals leading to the stabilization of mRNA transcripts of cytokines such as IL‐6 . Although the causal connection between the genetic variant and aberrant cytokine production was not explored mechanistically in this patient, nor was the distribution among the different cell types characterized, the demonstration of the abnormal cytokine secretion was necessary to guide the treatment to the appropriate biologic, as the identification of a genetic variant alone was insufficient to guide the treatment, making complementary strategies necessary …”
Section: Why When and How To Evaluate Cytokines?mentioning
confidence: 92%
“…Cycling increases healthcare and out-of-pocket costs when patients do not respond [ 24 , 25 ]. Furthermore, continuing to use a medication class that is not effective results in higher disease activity and reduces the patient’s quality of life [ 26 ]. After patients fail their first TNFi therapy, they are 27% more likely to inadequately respond to their second medication and three times more likely to discontinue therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the causal relationship between these "risk single nucleotide polymorphisms (SNPs)", genomic coordinates, and the final trait "disease" is robust, the whole picture of the relationship between genomic variation and treatment responsiveness has not been revealed. Several studies have reported gene polymorphisms involved in treatment responsiveness to specific drugs (e.g., steroids [15], methotrexate [16,17] TNF-α inhibitors [18,19], and IL-6 receptor inhibitors [20][21][22][23]), and these findings are awaiting further verification.…”
Section: Genome Epigenome and Gene Expression Signaturesmentioning
confidence: 99%